Identifikasi Ektoparasit pada Kelelawar di Gua Kenculit Desa Mekar Sari Kabupaten Lombok Tengah - Kencana, Bayu Tirta (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Kenculit cave is one of the caves in the southern region of Lombok Island which is known as a habitat for several types of small mammals, one of which is bats (order Chiroptera). The problem is that bats are one of the mammals that act as hosts for ectoparasites. The aim of the research was to determine the types of ectoparasites in bats in the kenculit cave in Mekar Sari Village, West Praya District, Central Lombok Regency. This type of research is an exploratory descriptive study designed using direct observation. The bat sampling technique uses the trapping method. Meanwhile, ectoparasite samples were taken by combing the bat's hair and then observing using a stereo microscope. Based on the research results, it shows that there are 3 types of ectoparasites from 2 different bat species, namely Taphozous melanopagon with 1 type of ectoparasite (Amblyomma sp.), and the Miniopterus pusillus bat species found with 2 types of ectoparasite (Cyclopodia sp. and Ancystropus sp.).